Marizomib alone or in combination with bevacizumab in patients with recurrent glioblastoma: Phase I/II clinical trial data. Issue 1 (2nd October 2021) - Bota, Daniela A; Mason, Warren; Kesari, Santosh; Magge, Rajiv; Winograd, Benjamin; Elias, Ileana; Reich, Steven D; Levin, Nancy; Trikha, Mohit; Desjardins, Annick
Abstract: Background: This phase I/II trial in patients with recurrent glioblastoma (GBM) evaluates the safety and preliminary efficacy of marizomib, an irreversible pan-proteasome inhibitor that crosses the blood–brain barrier. Methods: Part A assessed the safety and efficacy of marizomib monotherapy. In Part B, escalating doses of marizomib (0.5–0.8 mg/m 2 ) in combination with bevacizumab were evaluated. Part C explored intra-patient dose escalation of marizomib (0.8–1.0 mg/m 2 ) for the combination. Results: In Part A, 30 patients received marizomib monotherapy. The most common AEs were fatigue (66.7%), headache (46.7%), hallucination (43.3%), and insomnia (43.3%). One patient (3.3%) achieved a partial response. In Part B, the recommended phase II dose of marizomib was 0.8 mg/m 2 when combined with bevacizumab 10 mg/kg. In Part C, dose escalation to 1.0 mg/m 2 was not tolerated. Pooled analysis of 67 patients treated with marizomib ≤0.8 mg/m 2 and bevacizumab showed a nonoverlapping safety profile consistent with the known safety profile of each agent: the most common grade ≥3 AEs were hypertension (16.4%), confusion (13.4%), headache (10.4%), and fatigue (10.4%). The overall response rate was 34.3%, including 2 patients with complete response. Six-month progression-free survival was 29.8%; median overall survival was 9.1 months. Conclusions: The safety profile of marizomib as monotherapy and in combination with bevacizumab was consistent with previous observations that marizomib crosses the blood–brain barrier. Preliminary efficacy did not demonstrate a meaningful benefit of the addition of marizomib to bevacizumab for the treatment of recurrent GBM.